2016
DOI: 10.1073/pnas.1515941113
|View full text |Cite
|
Sign up to set email alerts
|

Representation of spontaneous movement by dopaminergic neurons is cell-type selective and disrupted in parkinsonism

Abstract: Midbrain dopaminergic neurons are essential for appropriate voluntary movement, as epitomized by the cardinal motor impairments arising in Parkinson's disease. Understanding the basis of such motor control requires understanding how the firing of different types of dopaminergic neuron relates to movement and how this activity is deciphered in target structures such as the striatum. By recording and labeling individual neurons in behaving mice, we show that the representation of brief spontaneous movements in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
177
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(198 citation statements)
references
References 50 publications
18
177
3
Order By: Relevance
“…The pairing of miRs base to the 3′‐UTR of their target mRNAs can cause mRNA destabilization or translation repression, which consequently inhibits mRNA expression (Fabian et al, ). Dopaminergic neurons in the nigral dopaminergic neurons are crucial to appropriate voluntary movement like the impairment of cardinal motor in PD (Dodson et al, ). Progressive, selective, and irreversible loss of these neurons in brain substantia nigra of rats will result in PD (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The pairing of miRs base to the 3′‐UTR of their target mRNAs can cause mRNA destabilization or translation repression, which consequently inhibits mRNA expression (Fabian et al, ). Dopaminergic neurons in the nigral dopaminergic neurons are crucial to appropriate voluntary movement like the impairment of cardinal motor in PD (Dodson et al, ). Progressive, selective, and irreversible loss of these neurons in brain substantia nigra of rats will result in PD (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Dodson and colleagues reported that most DA neurons in the SNc had a pause in activity during onset of movement [29]. Others have shown that increased SNc activity is critical for initiation and acceleration of movement [2,3032].…”
Section: Discussionmentioning
confidence: 99%
“…This work associates dorsal striatal phasic dopamine signaling with specific kinematic features of movement, consistent with other reports of movement-related phasic changes in nigrostriatal dopamine neuron firing. 43,44,45 …”
Section: Phasic Striatal Dopamine Signalingmentioning
confidence: 99%
“…This work associates dorsal striatal phasic dopaminergic signaling with specific kinematic features of movement, consistent with other reports of movement-related phasic changes in nigrostriatal dopamine neuron firing. [43][44][45] Phasic dorsal nigrostriatal dopaminergic signaling likely plays a critical role in important aspects of fine motor performance distinct from its well-established role in reinforcement learning based on primary rewards. Some conceptual models of nigrostriatal phasic signaling in motor performance suggest that dopaminergic signaling is involved in control of motor performance by matching sensory feedback about motor performance to internal representations of desired actions.…”
Section: Phasic Striatal Dopaminergic Signalingmentioning
confidence: 99%